Misi Micro:bit Cilik at SK Mambau: UiTM’S commitment to STEM education - Mohd Rick, Abd Malik; Hashim, Norhafizah; Abdul Rahman, Normaziah; Baharudin, Suzana (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The Misi Micro:bit Cilik program, organized by the Faculty of Computer and Mathematical Sciences (FSKM), UiTM Negeri Sembilan, was conducted in collaboration with the Robotics Club of Sekolah Kebangsaan Mambau through four workshop series between May and July 2025. The program involved 35 robotics club members aged 10 to 12 and aimed to introduce Micro:bit coding and its real-life applications while promoting creativity, teamwork, and problem-solving. Guided by UiTM lecturers, students participated in progressive hands-on activities, from learning basic inputs and outputs to developing creative STEM-based projects and presenting their final work during the closing session.